Adults with high functioning autism do not use vision for postural control - Morris, Susan; Parsons, Richard; Falkmer, Sture; Rosalie, Simon; Foster, C.; Falkmer, M. (2015)
Aim: Despite primarily a social disorder, most individuals with ASD also report difficulty with fundamental motor skills1,2. The development of motor skill relies on postural control and along with social skills is facilitated by the active use of visual information. The use of visual information for postural control in ASD has not been reported. The purpose of this study was to compare how adults with ASD and typically developed adults (TDA) use visual information to control posture during quiet standing. Method: The study used intermittent (15off, 5on) posterior neck vibration during 100 seconds of quiet stance to induce a postural illusion. In typically developed adults and only in the absence of vision this protocol induces a forward body lean. Participants (12ASD, 20 TDA) undertook four conditions combining vibration and visual occlusion. Results: Significant main effects were observed for group, F(1, 2355) = 5.50, p<.05, vibration illusion F(1, 2355) = 232.26, p<.0001, and visual occlusion condition F(3, 2355) = 4.22, p<.01. For both ASD and TDI the magnitude of postural movement during vibration under visual occlusion was in the order of between 7.8 and 10.2 mm. A significant interaction was also observed between group and visual occlusion condition F(3, 2355) = 10.11, p<.0001. The ASD group leaned forwards more than the TDI group when vision was either fully or partially available (EO-EO, EO-EC, EC-EO p<0.01); whereas, there was no difference between groups when vision was not available (EC-EC t=0.63 p=0.527). There were no differences in the postural position of the ASD group regardless of whether vision was fully, partially or not available (p>0.0335). Discussion: Our findings indicate that the individuals with ASD do not use visual information to control standing posture. In light of evidence of that vision-for-perception is processed typically in ASD, our findings support a specific deficit in vision-for-action. These findings may explain why individual with ASD experience difficulties with both social and motor skills since both require vision-for-action. Further research needs to investigate the division of these visual learning pathways in order to provide more specific intervention opportunities in ASD.